Data Contracts under Recent Developments of European Law: Novations and Paradoxes - Filatova-Bilous, Nataliia (Teisė, 2024)
The article analyses the most recent trends of data regulation in the EU and the peculiarities of data contracts. The latest regulations adopted or proposed in the EU set an access regime for data, which means that there is no exclusive owner of data, and data may be accessed and used by everyone participating in their production. This approach has caused significant changes in Contract Law regulating data contracts. The most prominent changes are the creation of distinct types of data contracts, the dissolution of the concept of privity, the application of unfair contractual clauses to B2B data contracts, and the facilitation of contractual and pre-contractual obligations with administrative sanctions. In the article, all these novations are critically analysed, and the conclusion is made that some of them constitute paradoxes for the classical Contract Law.